Fatigue and kinesiophobia in axial spondyloarthritis: Exploring the role of disease activity, functional impairment, and psychological factors - Gülay Alp; Fulden Sari (Ulusal Romatoloji Dergisi)
Objective: Fatigue and kinesiophobia are common in axial spondyloarthritis (axSpA) and may be influenced by disease activity, functional impairment, quality of life (QoL), and psychological factors. This study aimed to determine the prevalence of fatigue and kinesiophobia in patients with axSpA and to evaluate their associations with disease activity, functional status, QoL, and psychological variables. Methods: This cross-sectional study involved 134 patients with axSpA. Fatigue was assessed using the fatigue severity scale, and kinesiophobia was evaluated with the tampa kinesiophobia scale (TKS). At the same time, anxiety and depression were assessed using the hospital anxiety and depression scale. Structural equation modeling (SEM) was used to evaluate the mediating role of fatigue in the effect of anxiety and depression on kinesiophobia. Results: The mean age of the 134 patients was 38.3±10.4 years. Fatigue was observed in 60.6% of patients and kinesiophobia in 53.3%. Fatigue was more common among women, patients with higher body mass index, comorbidities, and those on non-steroidal anti-inflammatory drugs (NSAIDs). Patients with fatigue had higher disease activity, worse functional status, and reduced spinal mobility compared to those without fatigue. In multivariate analysis, QoL [odds ratio (OR)=1.36, 95% confidence interval (CI): 1.20-1.53] and erythrocyte sedimentation rate (OR=1.12, 95% CI: 1.00-1.26) were identified as independent predictors of fatigue. TKS score were moderately correlated with several measures of disease activity, functional impairment, and QoL. In multivariate analysis, QoL, anxiety, and NSAIDs use were independent predictors of kinesiophobia. SEM analysis showed that fatigue partially mediated the effects of anxiety on kinesiophobia, highlighting the contribution of psychological distress in movement-avoidance behavior. Conclusion: Fatigue and kinesiophobia are highly prevalent in axSpA and are closely linked to disease burden and emotional distress. These findings underscore the importance of addressing psychological factors to improve functional outcomes in axSpA.